FAKTOR-FAKTOR YANG MEMPENGARUHI PERTUMBUHAN LABA PADA PERUSAHAAN LQ45 DI BURSA EFEK INDONESIA - Junardi (FEB Universitas Sam Ratulangi Manado, 2023)
This research aims to evaluate the influence of Sales Growth, Firm Size, Total Assets Turnover, Net Profit Margin, and Inflation Rate on the profit growth of companies in the LQ45 index on the Indonesia Stock Exchange during the period 2017-2020. The research employs a quantitative method with documentation techniques using annual reports from the IDX website. From the results of descriptive statistical analysis, tests for normality, multicollinearity, heteroskedasticity, and autocorrelation, the data are deemed valid and proceed to regression analysis. The regression results indicate that Sales Growth has a significant positive influence on profit growth, while Firm Size, Total Assets Turnover, and Net Profit Margin do not significantly affect profit growth. Inflation Rate has a significant negative impact on profit growth.